Novel variants in COL2A1 causing rare spondyloepiphyseal dysplasia congenita - Zheng, Wen‐bin (Mol Genet Genomic Med, 2020)
BACKGROUND: Spondyloepiphyseal dysplasia congenita (SEDC) is an extremely rare inherited chondrodysplasia characterized by abnormal epiphyses, short stature, and flattened vertebral bodies. We investigate the phenotypes and the disease‐associated variants of SEDC in two unrelated Chinese families. METHODS: We identified disease‐associated variants in two nonconsanguineous families with SEDC using targeted next‐generation sequencing and confirmed the variants using Sanger sequencing. We investigated the phenotypes of the patients, including clinical manifestations, bone turnover biomarkers, bone mineral density and skeletal radiographic features. RESULTS: Two probands were diagnosed as SEDC according to the phenotypes of disproportionately short‐trunk stature, kyphosis, lumbar lordosis and adduction deformity of hips. Radiographs revealed kyphosis and lumbar lordosis, flattened vertebral bodies, compressed femoral heads and shortening of the femurs. Bone mineral density of the probands was lower than that of age‐ and gender‐matched normal children, but bone turnover biomarker levels were within normal range. Two novel heterozygous missense variants (NM_001844.5: c.1654 G>A, NP_001835.3: p.Gly552Arg; NM_001844.5: c.3518G>T, NP_001835.3: p.Gly1173Val) in collagen type II alpha 1 chain (COL2A1) were detected in the two families, which would impair the formation of stable triple‐helical type II collagen. CONCLUSIONS: We identified two novel disease‐associated variants in COL2A1, which led to severe SEDC. Our findings expanded the gene variant spectrum and phenotypic spectrum of extremely rare type II collagenopathies.